On the Role of Insula in Drug Addiction - Shah, Rajesh (Science Insights, 2023)
Drug addiction is a chronic, relapsing brain disease with limited treatment options and a high recurrence rate. Neuromodulation techniques, including repetitive transcranial magnetic stimulation, transcranial direct current stimulation, and deep brain stimulation, hold great therapeutic promise in the treatment of drug addiction. The insula is a key brain region in drug addiction, and its value as a neuromodulatory target in drug addiction needs further exploration. This article presents preclinical and clinical evidence for the role of the insula in drug addiction and explores its promise as a target for the treatment of drug addiction.